Analisis Penerapan Pedagogik Spiritualitas Berdasarkan Injil Matius Bagi Guru Pendidikan Agama Kristen Di Era Society 5.0 - Sariyanto Sariyanto (Sekolah Tinggi Teologi Aletheia, 2025)
Teaching Christian Education is often perceived as a routine transfer of knowledge, which can lead to suboptimal educational quality. In the era of Society 5.0, the challenge for educators is to inspire students to know Jesus as their Savior. In the context of the Industrial Revolution 5.0, Religious Education teachers must also respond to advancements in technology and artificial intelligence. This study aims to identify the pedagogical elements of spirituality found in the Gospel of Matthew. The methodology employed in this research is descriptive qualitative through literature study. The findings indicate that the application of pedagogical spirituality, such as prioritizing the kingdom of God, building a relationship with God through prayer, and following the example of Jesus, can enhance the quality of teaching. This study emphasizes the importance of integrating spiritual values into education to develop students' holistic character, preparing them to face the challenges of the modern era.